In-Vivo Biodistribution and Safety of 99mTc-LLP2A-HYNIC in Canine Non-Hodgkin Lymphoma - Zwingenberger, Allison L.; Kent, Michael S.; Liu, Ruiwu; Kukis, David L.; Wisner, Erik R.; DeNardo, Sally J.; Taylor, Sandra L.; Chen, Xiucui; Lam, Kit S. (PLOS ONE, 2012)
Theranostic agents are critical for improving the diagnosis and treatment of non-Hodgkin Lymphoma (NHL). The peptidomimetic LLP2A is a novel peptide receptor radiotherapy candidate for treating NHL that expresses the activated α4β1 integrin. Tumor-bearing dogs are an excellent model of human NHL with similar clinical characteristics, behavior, and compressed clinical course. Canine in vivo imaging studies will provide valuable biodistribution and affinity information that reflects a diverse clinical population of lymphoma. This may also help to determine potential dose-limiting radiotoxicity to organs in human clinical trials. To validate this construct in a naturally occurring model of NHL, we performed in-vivo molecular targeted imaging and biodistribution in 3 normal dogs and 5 NHL bearing dogs. 99mTc-LLP2A-HYNIC-PEG and 99mTc-LLP2A-HYNIC were successfully synthesized and had very good labeling efficiency and radiochemical purity. 99mTc-LLP2A-HYNIC and 99mTc-LLP2A-HYNIC-PEG had biodistribution in keeping with their molecular size, with 99mTc-LLP2A-HYNIC-PEG remaining longer in the circulation, having higher tissue uptake, and having more activity in the liver compared to 99mTc-LLP2A-HYNIC. 99mTc-LLP2A-HYNIC was mainly eliminated through the kidneys with some residual activity. Radioactivity was reduced to near-background levels at 6 hours after injection. In NHL dogs, tumor showed moderately increased activity over background, with tumor activity in B-cell lymphoma dogs decreasing after chemotherapy. This compound is promising in the development of targeted drug-delivery radiopharmaceuticals and may contribute to translational work in people affected by non-Hodgkin lymphoma.